Money in sports - Hunter, Nick (Chicago, Ill Heinemann Library, 2012)
Examines how money has become tied to sports in a variety of ways, and what implications this has for both athletes and fans
A gift from book Africa
Sports
1 2 13
NEW_ZTN_GN
Keywords: Professional sports -- Economic aspects; Sports -- Economic aspects; Sports -- Moral and ethical aspects